Acute electrical muscle stimulation effects on strength and anaerobic power in soccer players - Sofuoğlu, Cem; Fujita, Rafael Akira; Keskin, Kadir; Kamiş, Okan; Akçay, Neslihan (International Journal of Sports Medicine)
Anaerobic power and lower limb muscle strength are of great importance in soccer and various preloading strategies are used to improve these abilities. We investigated the acute effects of electrical muscle stimulation (EMS) on muscle strength and anaerobic power in soccer players. Nineteen healthy male soccer players (age=21.1±1.6 years; training experience=10.1±3.2 years; height=178.1±4.0 cm; body mass=8.9±3.7 kg) participated in the study. A placebo effect was created without telling the participants the which current (intensity) was applied. After the current applied to the quadriceps muscles, strength and anaerobic power tests were performed. Perceived exertion assessment was also collected after the performance tests. The 75Hz current showed better performance in dominant (p<0.001, d=0.75) and non-dominant (p<0.001, d=0.69) quadriceps muscle group strength (kg). The 75Hz current condition peak power had significantly higher values than 15Hz (p<0.05, d=0.38) and 104Hz conditions (p<0.05, d=0.60). Therefore, the 75Hz current was the most successful in improving lower extremity and anaerobic power performances of soccer players. Future research should examine how to utilize sport-specific abilities related to strength and anaerobic power in soccer players for longer periods at peak.